PIBID as a public policy for teaching initiation: a gaze at the formative processes in narrative writing (Práxis Educativa, 2024)
In this paper, the experience in the Programa Institucional de Bolsa de Iniciação à Docência (PIBID) [Teaching Initiation Scholarship Institutional Program] and its contributions to initial teacher training are discussed. Narratives that register the encounter of a Pedagogy student with everyday school life were taken for analysis, through the aforementioned program in the subproject developed by the Federal University of Tocantins. The narratives were analyzed based on the concept of perejivanie (Vygotsky, 2018), with the aim of understanding the situations experienced in PIBID that are shown, in narrative writing, to enhance the professional development of future teachers. It was verified PIBID’s ability to promote constant relationships between the actors involved in school education and to provide remarkable events, episodes full of possibilities and emotional collisions for pre-service teaching undergraduate students that contribute to the development of their being a teacher,Keywords: Initial education. Narrative. PIBID.